PENGARUH PERKEMBANGAN KEPARIWISATAAN DAN SISTEM KEKERABATAN TERHADAP SISTEM BAGI HASIL USAHA TANI PADI SAWAH DI BALI - Budi Susrusa, Ketut; Iqbali, Saptono (PIRAMIDA; Vol. 4, No. 1 Juli 2008, 2012)
High population growthled to a scarcity of arable land in Indonesia. During 1963-1993periods, farmer households have increased 1.77% i.e, almost three times than the extend ofagricultural land. Soe, the land that is held by the farmer households were not only decreased inits size, but also increased in its inequality. Furthermore, this phenomenon encouraged theexistence of share cropping contract. Sharecropping contract is an old institution that was knownsince Babylonian era ( ± 2300 BC) and still showing controversial issues related to agriculturalproductivity. Certainly, the institution that was born in along history of mankind could not beeasily change, however some modification should be conducted along with the implementation ofrecent agricultural debelopment programs.The objectives this study was identify the change of sharecropping contract on ricefarming along with development of economy in Bali which was also stimulated by development oftourism and to learn weather or not sharecropping contract was contra productive in terms laborused and farming performance.This study was conducted at the subaks area, three within and three others of tourismarea. The population was classified into three group, owner-cultivator, non-kinship-sharecrpper,kinship- sharecropper. Farming intensity was measured by the indicator of the used of labor andinputs, whereas farm performance will be evaluated by land productivity and farm income.This study reveals that the more developed economy within a region, the better sharecropper’ sbargaining position. Furthermore, kinship-sharecropping contract was as not bad as the generalopinion that is not agreed to sharesropping contract.Labor utilization and farm performance both in kinship sharecropping were consistentwith enforceable contract that is led to optimizing input allocation. From the view points ofowners-sharecropping relationships it was indicated that the owners held control upon theallocation of farm inputs.
Keywords: farmer households, sharecropping, agricultural development, labor, farm income.